PENJATUHAN HUKUMAN MATI TERDAKWA KORUPSI PADA MASA PANDEMI COVID-19 - Jean Marie Yemima (2022)
The COVID-19 pandemic that has infected the entire world, Indonesian without exception, has left many impacts on people's lives. One of the most impactful is on economic field. The implementation of Large-Scale Social Restrictions makes almost all business sectors, both large and small has terrible loss, creating a very high wave of layoffs. In these difficult conditions, Indonesia's old disease emerged which immediately angered the public, namely corruption. The community also asked for at least the perpetrators to be put to death. In article 2 paragraph (2) of Law number. 31 of 1999 and Law number 20 of 2001 concerning the Crime of Corruption states that corruptors can apply the death penalty, but with certain conditions as a condition. Because there is already have a legal basis, the death penalty should be applied by perpetrators of criminal acts of corruption, however, there are several obstacles that prevent this crime from being carried out. This research uses a normative research method with a literature study that analyzes the Corruption Crime Act, as well as related laws such as Perppu no, 1 of 2020, the Criminal Code, and so on. The conclusion of this research is that the Death Penalty for Corruptors can be applied by looking at the juridical regulations, from the philosophical and sociological side. So far, there has been no application of the death penalty to perpetrators of corruption. This is hindered by various fields, either in other regulations or in human rights issues